Understanding Sustainability Through Mindfulness: A Systematic Review - Tezel, Ecem; Giritli, Heyecan (Springer International Publishing, 2018)
The construction industry is central to how the future of humanity will be shaped and can be sustained. Sustainable development and construction is the responsibility not only of researchers, but also all stakeholders involved in the creation and use of the built environment. Despite increasing global awareness on environmental issues, creating a sustainable built environment seems not to be easy. This may be attributed to the gap between the possession of environmental knowledge and environmental awareness, and displaying pro-environmental behavior. It is epitomized by the attitude, “I know I should, but I don’t.”; exemplary, even replacing shorter automobile trips with walking or cycling may cause reduction on environmental impact, driving is the overall tendency of individuals. The characteristic of such an attitude, mindfulness, is ascribed to people who have a relatively greater awareness of the surroundings and of other people. Although mindfulness research has seen exponential growth in the last two decades, a limited number of studies has been adapted towards environmental purposes. This study aims to assess the link between mindfulness and sustainable behavior. In the study, a meta-analytical approach will be adopted, which assumes the conceptualization of mindfulness as a form of behavioral regulation, and the relationship between mindfulness and pro-environmental behavior.